Transformation of The Taxation System in The Context of The Coronavirus Crisis in Order to Ensure the Economic Security of Business Entities and The Nation State - Yulia Alexandrovna NAZAROVA; Natalia Sergeevna SHCHERBAKOVA; Ivan Olegovich GORUNOV (Communications of International Proceedings, 2021)
The purpose of the article is to consider amendments to the tax system in view of the impact of the crisis phenomena, particularly those caused by the 2020 pandemic. The authors analyze international experience of supporting business and citizens in the pandemic. The Russian Federation provides information on the most affected sectors and measures taken by the government. The article provides the list of coronavirus effects influencing the economic security of the nation state. Based on the research, the authors draw conclusions on two aspects of the tax system transformation during the pandemic: on the one hand, the authorities take fiscal support measures for certain industries and population groups; on the other hand, these measures lead to budget deficits and greater amendments to the tax system in the medium term, which are higher tax rates and tightened fiscal policy.
Keywords: Taxation system; tax system transformation; coronavirus crisis; list of coronavirus effects; international experience of supporting business; fiscal support measures; budget; taxes.